Héritages, réceptions, écoles en sciences du langage : avant et après Saussure - Laura Iseut Lafrance St-Martin (Communiquer)
This collective book, which pays tribute to linguistics professor Christian Puech, aims to provide an “overview” of the discipline. The book consists of 31 short texts with little connection between them, which are divided into 7 sections. Each section aims to account for the variety of Puech’s research interests by following an approximately chronological order of the discipline’s evolution.